2000
DOI: 10.1016/s0960-9822(00)00475-9
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-kinase regulates Raf1 through Pak phosphorylation of serine 338

Abstract: We have previously shown that inhibition of phosphatidylinositol (PI) 3-kinase severely attenuates the activation of extracellular signal-regulated kinase (Erk) following engagement of integrin/fibronectin receptors and that Raf is the critical target of PI 3-kinase regulation [1]. To investigate how PI 3-kinase regulates Raf, we examined sites on Raf1 required for regulation by PI 3-kinase and explored the mechanisms involved in this regulation. Serine 338 (Ser338), which was critical for fibronectin stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
133
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(146 citation statements)
references
References 18 publications
11
133
1
1
Order By: Relevance
“…PI3K has been shown to stimulate integrin-mediated Raf activation in synergy with Ras (Chaudhary et al, 2000). Cooperative effects between these two signaling cascades have also been demonstrated in the regulation of the platelet-derived growth factor-induced proliferation (Choudhury et al, 1997) or in cell cycle progression and transformation (Sheng et al, 2001a, b).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K has been shown to stimulate integrin-mediated Raf activation in synergy with Ras (Chaudhary et al, 2000). Cooperative effects between these two signaling cascades have also been demonstrated in the regulation of the platelet-derived growth factor-induced proliferation (Choudhury et al, 1997) or in cell cycle progression and transformation (Sheng et al, 2001a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The recent suggestion that P13-K and Pak3 regulate Raf-1 activity through S338 phosphorylation (7,25,49) a good deal of attention. We have tested this model using a monoclonal antibody that is highly specific for S338 phosphorylation on Raf-1 (40) and found, in contradiction to the conclusions of Sun et al (49), that S338 phosphorylation could still be observed when P13-K activity was inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…There is much interest in the cross talk that exists between these different, parallel Ras pathways, and in some but not all cell types, inhibition of Pl3-K that leads to suppression of ERK has been shown (8,16,24,56). In different studies, Pl3-K has been shown to regulate ERK activation at the level of Ras or at the level of Raf-1 (7,8,27,56). More recently, it was suggested that Pl3-K regulates Raf-1 by activating protein kinases that can phosphorylate Raf-1 directly.…”
mentioning
confidence: 99%
“…5 Phosphorylation at S338 is critical for Raf-1 activation and ERK stimulation by a variety of factors including activated integrins and growth factors. 6,7 Maximal Raf-1 activation is achieved by concurrent phosphorylation at Y341 and S338. 8 While concordant data indicates Src as the kinase phosphorylating Raf-1 at Y341, it is still controversial which is the kinase phosphorylating Raf-1 at S338.…”
Section: Introductionmentioning
confidence: 99%
“…9 Phosphatidyl-inositol-3-kinase (PI3-K) inhibitors (Wortmannin and Ly-294002) were shown to inhibit both Raf-1 kinase activity and its phosphorylation at S338, stimulated by EGF and by integrins in COS-7 cells. 6,10 However, a careful re-examination of those results raised some doubts on the effective role proposed for Pak3. Chiloeches et al argued against the physiological role proposed for Pak3, mainly because supporting data were obtained by overexpression of recombinant factors or by using PI3-K inhibitors at concentrations that block also Ras activity.…”
Section: Introductionmentioning
confidence: 99%